EVALUATION OF PATIENT’S LIFE QUALITY AFTER SIMULTANEOUS PANCREAS AND KIDNEY TRANSPLANTATION - N. V. Zagorodnikova; R. V. Storozhev; Yu. A. Anisimov; K. E. Lazareva; I. V. Dmitriev; O. Yu. Mikita; А. V. Pinchuk (Трансплантология (Москва), 2017)
Introduction: the use of standardized questionnaires for  assessment of patients’ life  quality after organ transplantation has not been widely used in our country.Purpose: The assessment of patients’ quality of life after the simultaneous pancreas & kidney transplantation using the SF-36 questionnaire.Material and methods: 35 patients with type I diabetes mellitus (DM1) complicated by end-stage chronic renal failure were investigated. There were 16 women (45.7%) and 19 men  (54.3%). The median age was 36 [33; 45] years. The patients were divided into 2 groups depending on the transplantation type:  group I included the patients who underwent isolated kidney transplantation, group  II  included those  after combined kidney and  pancreas transplantation. Patients’ life quality was estimated using the SF-36 questionnaire.Results: Patients in group II had significantly better physical functions, general health  status, and vital activity.Conclusion: Simultaneous pancreas & kidney transplantation considerably improves the life quality of patients with DM1.